Les 20 printemps des jardins partagés français. Bilan et perspectives - Laurence Baudelet-Stelmacher (In Situ)
The French community gardening movement started in 1997 with the drawing up of a founding text on all forms of gardens and of a ‘shared earth’ charter, ‘La Terre en partage’. A national network, called ‘Le Jardin dans tous ses états’, was set up with financial support from the ‘Fondation de France’, a national trust federating charities and philanthropic organisations. The first community garden, ‘Le Jardin des (Re)trouvailles’ was opened in Lille in its Moulins neighbourhood. Within the space of a generation, the movement has grown dramatically in large cities, but it has also developed in rural areas such as the Occitanie region, for example, and in Brittany. This article tells the story the emergence of this community gardening movement in France, its protagonists and the historical context of its birth.